A digestive cartridge reduces intestinal injury in a murine model of necrotizing enterocolitis - Sarah Z. Wang; Djanira Fernandes; Savas T. Tsikis; Thomas I. Hirsch; Amy Pan; Mikayla Quigley; Valeria Ruiz; Scott C. Fligor; Carter R. Petty; Greta Loring; Stephen Davia; Juhye Kang; et al. (PLoS ONE, 2026)
Background Formula feeding is associated with necrotizing enterocolitis (NEC), a life-threatening gastrointestinal illness affecting premature infants. The presence of undigested fat in enteral formula may mediate NEC severity. The immobilized lipase cartridge (ILC) is an FDA-cleared digestive device that hydrolyzes triglyceride fat in formula into readily absorbable free fatty acids and monoglycerides. We hypothesized that use of a new ILC prototype designed to support increased feeding frequency in infants will reduce NEC mortality and disease severity in a murine model. Methods NEC was induced in C57BL/6J mice from post-natal day 4–6 via oral gavage of lipopolysaccharide-containing formula 4x/day and hypoxia (5% O 2 ) exposure 2x/day. Littermates were randomized to one of five groups: dam-fed (normal controls), ILC-digested formula, placebo-processed formula, NEC + ILC-digested formula, NEC+placebo-processed formula. Weights and mortality were measured daily. Mice were euthanized on P7 for assessment of NEC severity. Results Normal controls had better survival rates than formula-fed and NEC mice. The NEC + ILC group exhibited lower clinical and histologic severity scores compared to the NEC+placebo group on masked evaluation. Conclusion The administration of formula pre-digested by the ILC improved clinical sickness, gut appearance, and histologic severity of NEC compared to placebo. These findings support further investigation of the ILC as a non-invasive, preventive therapy for NEC in humans.